2010
DOI: 10.1128/jb.00410-10
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tropodithietic Acid Biosynthesis Is Controlled by a Novel Autoinducer

Abstract: The interactions between marine prokaryotic and eukaryotic microorganisms are crucial to many biological and biogeochemical processes in the oceans. Often the interactions are mutualistic, as in the symbiosis between phytoplankton, e.g., the dinoflagellate Pfiesteria piscicida and Silicibacter sp. TM1040, a member of the Roseobacter taxonomic lineage. It is hypothesized that an important component of this symbiosis is bacterial production of tropodithietic acid (TDA), a biologically active tropolone compound w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(113 citation statements)
references
References 47 publications
3
107
2
1
Order By: Relevance
“…It has been demonstrated that TDA induces its own production in Ruegeria (Silicibacter) sp. TM1040 (Geng and Belas, 2010), and we speculate that this would also be true for the R. mobilis strains of the present study.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…It has been demonstrated that TDA induces its own production in Ruegeria (Silicibacter) sp. TM1040 (Geng and Belas, 2010), and we speculate that this would also be true for the R. mobilis strains of the present study.…”
Section: Discussionmentioning
confidence: 75%
“…It has been hypothesized that QS regulates the production of TDA (Geng and Belas, 2010;Berger et al, 2011). One of the classical groups of QS molecules, the AHLs, was not detected in any of the tested R. mobilis strains.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations